2021
DOI: 10.28982/josam.907597
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings, treatments and obstetric results of pregnant women diagnosed with coronavirus disease 2019

Abstract: Background/Aim: Coronavirus disease 2019 , which causes acute respiratory disease, is an emergency that concerns global public health. Limited data are available on coronavirus disease 2019 in pregnant women. We aimed to evaluate the characteristic features and perinatal results of pregnant women diagnosed with COVID-19. Methods: This retrospective cohort study was conducted in a Training and Research Hospital. Clinical records and perinatal results of 84 pregnant women and 46 newborns diagnosed with coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…De la Gatta et al [14] and Elçi et al [15], have found a predominance of third trimester in pregnant Covid-19 infected patients, issue alike to this investigation in which most of pregnant women admitted had a gestational age of 24 weeks or more. Factors associated to increased risk of infection during pregnancy are well known [16], and this issue has called the attention of others investigators.…”
Section: Discussionsupporting
confidence: 78%
“…De la Gatta et al [14] and Elçi et al [15], have found a predominance of third trimester in pregnant Covid-19 infected patients, issue alike to this investigation in which most of pregnant women admitted had a gestational age of 24 weeks or more. Factors associated to increased risk of infection during pregnancy are well known [16], and this issue has called the attention of others investigators.…”
Section: Discussionsupporting
confidence: 78%